Service quality in private higher education industry: The students' perceptions and expectations / Noraini Yaumiddin - Yaumiddin, Noraini (2010)
Higher education has evolved from a public service to a business entity. As other trades in the business world, private higher education institutions need revenue to sustain existence. Revenue can only gained by offering high quality and competitive service. Determinants of quality need to be identified and these determinants then used as criteria to measure the quality of service delivery of a particular institution. This study looks into the service quality of a private university in Selangor from the perspective of the students. The instrument used in this study is HEdPERF which was adapted from SERQUAL. A group of students from Faculty of Education and Language Studies, Universiti Industri Selangor, a private university owned by the state government of Selangor was chosen to participate in this study. In measuring service quality level, students' expectations and perceptions of the university are solicited. The findings revealed that students are generally dissatisfied with the service delivery of the university especially in the aspect of how the university handles feedback for improvement given by the students. Nevertheless, students are relatively satisfied with the service delivery of the academic staff. It is advisable for private higher institutions to pay heed to students' feedback and provide a proper channel for students to do so. The quality measuring procedures should be practiced at a regular basis by private higher institutions to ensure their service level remain excellent which will help these institutions to maintain its survival.